Dynamics of three wave stochastic decays in nonlinear matter - Buts, V.A.; Kovalchuk, I.K. (Вопросы атомной науки и техники, 2016)
In the present work the transition of decay instability into stochastic regime in a nonlinear media is analyzed for a
magnetoactive plasma and for the ferrite magnetized to the saturation level. It was shown that parameter of
nonlinear interaction can be anomalously strong near the resonance frequencies: electron and ion cyclotron
frequencies in the magnetoactive plasma and ferromagnetic frequency in ferrite. It was shown that the threshold
value of decaying wave amplitude, when transition into stochastic regime takes place, is reducing when frequency of
the wave with the lowest frequency is decreasing. Анализируется переход распадной неустойчивости в стохастический режим в нелинейных средах:
магнитоактивной плазме и намагниченном до насыщения феррите. Показано, что параметр нелинейного
взаимодействия может быть аномально большим вблизи резонансных частот: электронной и ионной
циклотронной в магнитоактивной плазме и частоты ферримагнитного резонанса в феррите. Отмечено, что с
уменьшением частоты самой низкочастотной волны, участвующей в распаде, уменьшается пороговое
значение амплитуды распадающейся волны, при котором происходит переход в стохастический режим. Аналізується перехід розпадної нестійкості в стохастичний режим у нелінійних середовищах:
магнітоактивній плазмі і намагніченому до насичення фериті. Показано, що параметр нелінійної взаємодії
може бути занадто великим поблизу резонансних частот: електронної та іонної циклотронної в
магнітоактивній плазмі та частоти феромагнітного резонансу у фериті. Відзначено, що зі зменшенням
частоти самої низькочастотної хвилі, що бере участь у розпаді, зменшується порогове значення амплітуди
хвилі, що розпадається, при якому відбувається перехід у стохастичний режим.